Assessment of genetic diversity in West Coast Tall coconut (Cocos nucifera) - SUDHA, R; NIRAL, V; DIWAKAR, Y; RAJESH, M K; SAMSUDEEN, K (The Indian Journal of Agricultural Sciences, 2019)
Coconut palm (Cocos nucifera L.) is an important perennial oil-yielding plantation crop in the tropics. It is crosspollinated and exhibits high level of genetic variation among cultivars in terms of colour, size and shape of the fruits. The objectives of the study were to estimate the magnitude of genetic variability, heritability and genetic advance for vegetative, reproductive and fruit component parameters of the eleven parents and progenies (93) of West Coast Tall (WCT) coconut, and analyse genetic diversity using molecular markers. The experiment was undertaken during 2017-2018 at ICAR-Central Plantation Crops Research Institute, Kasaragod, Kerala. Results revealed that, medium phenotypic and genotypic co-efficient of variation (PCV and GCV) were observed for all studied vegetative and reproductive characters except length of the leaves, total number of bunches, number of female flowers/bunch and number of nuts/palm. High heritability and genetic advance as percent of mean was observed for number of leaves, length of leaf, length of spikelet bearing portion, number of female flowers/inflorescence, length of inflorescence, weight of husked fruit and whole fruit, indicating that most likely the heritability is due to additive gene effects and thus the chances of fixing by selection will be more. Thus, these characters are to be given importance in the breeding for yield improvement in coconut. Based on the molecular data, Jaccards similarity coefficient values were generated and it ranged from 0.54 to 0.96. The information provides the quantum of inheritance of genetic makeup in different groups and it could have practical significance in crop improvement programmes.